Pengaruh Current Ratio, Debt To Equity Ratio, Dan Return On Equity Terhadap Financial Distress - Dipta Adytia Nugraha; Nursito Nursito (COSTING : Journal of Economic, Business and Accounting, 2021)
This study aims to examine the effect of CR, DER and ROE on Financial Distress in the Automotive and Components subsector companies listed on the Indonesia Stock Exchange for the period 2015-2019. Sampling using purposive sampling and found 8 companies that meet the criteria of 13 companies as a sample. So that the sample studied was 40 data for 5 years. This research method uses the quantitative method of descriptive and verification approaches. Based on the results of tests conducted using SPSS it can be concluded with the T test, and the F Test that is CR and DER does not affect Financial Distress, while ROE affects Financial Distress. with the results of simultaneous research that CR, DER and ROE affect Financial Distress. and the Determination Coefficient study in this study also found that CR, DER and ROE together can explain Financial Distress of 27.7% and there are still 72.3% of other factors that influence Financial Distress. Keywords: CR, DER, ROE, Financial Distress